THE ROLE OF SOCIAL MEDIA IN PROMOTING BULUKUMBA TOURISM - Nur Alam; Mukhlis Amin (Journal of Information Technology and Its Utilization, 2020)
In connection with the growing development of the internet and its use, especially social media, it makes almost all aspects of life inseparable from it, including the tourism sector. This research examine the role of social media in developing tourism in Bulukumba. This study wanted to know whether social media had a role in promoting and providing information about tourism in Bulukumba. This study examines the role of social media in the promotion of tourism in Bulukumba using a quantitative approach. We collect data by surveying tourists using a questionnaire. In addition, we also observed official government social media accounts. The results showed that social media has a role in promoting tourism in Bulukumba. Second, the official social media accounts belonging to the Tourism Office seem to have no role in tourism promotion. This is due to poor management.